2015
DOI: 10.1111/1753-0407.12294
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes, diagnosed and undiagnosed diabetes, their risk factors and association with knowledge of diabetes in rural Bangladesh: The Bangladesh Population‐based Diabetes and Eye Study

Abstract: In this rural Bangladeshi community, UDM was high. Lower socioeconomic status was associated with a higher risk of UDM. Overall knowledge of DM was poor. Public health programmes should target those of low socioeconomic status and aim to increase knowledge of DM in rural Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 20 publications
4
33
1
2
Order By: Relevance
“…This paper is based on data obtained in the first phase of the project. The first phase of the BPDES targeted adults aged between 30–89 years to determine their knowledge, attitudes, and practice about diabetes and common eye diseases, measuring fasting blood glucose to estimate known and undiagnosed type 2 diabetes [11] and blood pressure to estimate known and undiagnosed hypertension [7] and information on disability. The study location is approximately 200 km southwest of the capital city of Dhaka, with eligible participants of approximately 5,500 in the Banshgram Union [22].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper is based on data obtained in the first phase of the project. The first phase of the BPDES targeted adults aged between 30–89 years to determine their knowledge, attitudes, and practice about diabetes and common eye diseases, measuring fasting blood glucose to estimate known and undiagnosed type 2 diabetes [11] and blood pressure to estimate known and undiagnosed hypertension [7] and information on disability. The study location is approximately 200 km southwest of the capital city of Dhaka, with eligible participants of approximately 5,500 in the Banshgram Union [22].…”
Section: Methodsmentioning
confidence: 99%
“…Narail is considered to be a typical rural district, being neither in a remote area nor in close proximity to metropolitan Dhaka. The similarity of study participants with the population at national level has been reported elsewhere [11, 21]. The sample size was based on the 2012 prevalence of type 2 diabetes (6.3%) among adults in Bangladesh, as estimated by the International Diabetes Federation’s Diabetes Atlas [23].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of undiagnosed diabetes is similar to values reported in a higher risk cardiac bypass population by Lauruschkat et al (5) (5.2%). The Bangladesh Population-based Diabetes and Eye Study (25) recently reported a 3.6% prevalence of undiagnosed diabetes, based on a random sampling strategy. Prevalence rates in the general population appear to be lower, with reported 1.13% undiagnosed type 2 diabetes in the Canadian Health Measures Survey (26), 2.7% in the Third National Health and Nutrition Examination Survey in the U.S. (19), and 2.6% prevalence in rural communities in Sudan (27).…”
Section: Discussionmentioning
confidence: 99%